Consumerism - Espejo, Roman , 1977- (Opposing viewpoints series, 2010)
From the Publisher: Each volume in the Contemporary Issues Companion series provides readers with a wealth of information on topics of current interest. Focusing on important social issues, each anthology examines its subject in a variety of ways, from personal statistical articles to the most relevant commentaries and overview. Every essay is introduced with a brief summary of its main points and biographical information about the author, while the book?s introduction presents a broad overview of the issues discussed. A perfect resource for both students and the general reader, the Contemporary Issues Companion series is sure to be a valued source of current and readable information